Financial Ratio Analysis to Measure Company Performance - Academy, Gayatri (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
This study aims to determine the achievement of financial performance in companies in the retail trade sector listed on the Indonesia Stock Exchange in 2018-2022. This study use a population of all Financial Statements for companies in the retail trade sector and the sample is the Balance Sheet and Income Statement for 2018-2022. The data analysis technique used in this study is ratio analysis consisting of liquidity ratios, solvency, activity and profitability ratios.The results of this study indicate that of the five companies when viewed from the aspect of good liquidity ratios only PT. Ace Hardware. If based on the debt to asset ratio and debt to to equity ratio the five companies show good financial performance. If seen from the fixed asset turnover of the five companies the financial performance is not good. If based on the total asset turnover PT Sumber Alfaria Trijaya and The PT Ace Hardware Indonesia show good financial performance. If based on the NPM the five companies show good financial performance. If seen from the GPM of the five companies that show good financial performance, namely PT Midi Utama Indonesia and PT MAP Aktif Adi Perkasa. If based on the ROE of the five companies showing good financial performance.